A patient with a red eye and pulmonary oedema. (3rd March 2014) - Kanji, R; Ghonim, S; Robertson, A; Dubrey, S W
Abstract : A middle-aged black male patient presented with symptoms and radiological features indicative of pulmonary oedema. Following several admissions for the same symptomology, and poor resolution of chest radiographic features, the patient developed a red eye. The latter was diagnosed as uveitis, which prompted consideration and proof of a diagnosis of cardiopulmonary sarcoidosis. The patient was subsequently treated with high dose steroids resulting in a partial recovery, complicated by issues of fluid retention.